Lavender Oil Massage Therapy to Treat Restless Legs Syndrome Symptoms in Chronic Kidney Disease Patients - Azizi, Putri Dwi; Nurhusna, Nurhusna (Sarana Ilmu Indonesia (salnesia), 2025)
Massage therapy can be used to reduce symptoms of Restless Legs Syndrome (RLS). Massage therapy is a light touch and massage technique that can increase relaxation in the body by triggering a feeling of comfort through the skin surface and reducing pain, this is because massage stimulates the body to release endorphin compounds. The purpose of this study was to describe the symptoms of Restless Legs Syndrome (RLS) in Chronic Kidney Disease (CKD) patients before and after receiving lavender oil massage therapy. This study used a case report design. The subjects were Chronic Kidney Disease (CKD) patients with symptoms of Restless Legs Syndrome (RLS). The data were analyzed descriptively by comparing RLS symptoms before and after the lavender oil massage therapy. Data were conducted using descriptive analysis by looking at the symptoms of Restless Legs Syndrome (RLS) before and after massage therapy. The findings showed that after lavender oil massage therapy was applied twice in conjunction with hemodialysis sessions, RLS symptom scores decreased from 29 (severe) to 20 (moderate). The application of lavender oil massage therapy can reduce RLS symptoms in CKD patients, so massage therapy can be used as an intervention to reduce RLS symptoms.